Entre laços e nós: (im)possibilidades de um psicanalista nos espaços de Educação Permanente em Saúde - Fiochi, Paula Ione Costa Quinterno [UNESP] (2015)
This study aims to discuss the (im)possibilities of a psychoanalyst's praxis within the context of Permanent Education in Health. In these spaces, namely, the Núcleo de Educação Permanente em Saúde (Center of Permanent Education in Health) and the Centro Integrado de Humanização (Integrated Center for Humanization), the psychoanalyst was not summoned as such, being considered a plus-onein these groups. Psychoanalysis as a discursive and dialectic experience has offered base support for our practice. The references of Jacques Lacan's psychoanalysis on the Theory of Four Discourses, the concept of Subject and Psychoanalytic Act, along with the idea of education and training, grounded our practice both with the subjects of the groups and as being the researcher at this thesis. In this sense, we discuss the possibilities of listening to the subject of psychoanalysis as well as to the discourse passages in these formation spaces. The Permanent Education in Health policy and its operation were taken on two levels of analysis: a political-ideological level and the subjects' praxis in these spaces level.Both direct the (im)possibilities of the psychoanalyst's intercession. From their action point of view, the psychoanalyst is guided by the discourse of the analyst, although it is not in intention. It is by the psychoanalysis ethics or the desire ethics that we can sustain our practice towards the questioning of knowledge, S2, of the University Discourse, to try, as a plus-one, to meet the knowledge that matters, knowledge from the subject themselves, the not-known of the experience, creating opportunities for another social bond, the Discourse of the Hysteric. Therefore, from the experience of a psychoanalyst this work seeks to discuss possibilities for dialogue between the practice of psychoanalysis and Permanent Education in Health